2021
DOI: 10.1371/journal.pone.0260278
|View full text |Cite
|
Sign up to set email alerts
|

Supporting adolescents living with HIV within boarding schools in Kenya

Abstract: Adolescents and youth living with HIV (AYLHIV) are a uniquely vulnerable population facing challenges around adherence, disclosure of HIV status and stigma. Providing school-based support for AYLHIV offers an opportunity to optimize their health and wellbeing. The purpose of this study was to evaluate the feasibility of school-based supportive interventions for AYLHIV in Kenya. From 2016–2019, with funding from ViiV Healthcare, the Elizabeth Glaser Pediatric AIDS Foundation implemented the innovative Red Carpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 31 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…The reverse interpretation, that HIV stigma may result in AYWHIV dropping out of school suggests that the support for the AYWHIV to remain in school should include measures that mitigate the impact of HIV stigma in the school environment. Measures already tested in our setting include increasing HIV literacy among school staff, specific HIV treatment support measures in school like confidential treatment storage, linkages between schools and health facilities and psychosocial support [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse interpretation, that HIV stigma may result in AYWHIV dropping out of school suggests that the support for the AYWHIV to remain in school should include measures that mitigate the impact of HIV stigma in the school environment. Measures already tested in our setting include increasing HIV literacy among school staff, specific HIV treatment support measures in school like confidential treatment storage, linkages between schools and health facilities and psychosocial support [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like other regions in Kenya, AYWHIV in Western Kenya go through the public school system, with a substantial proportion attending high schools with boarding facilities. The boarding schools especially pose a challenge for the learners in terms of storage of medication and keeping to required schedules for taking them medication and clinic attendance [ 47 ]. HIV care is largely provided through the donor-funded public health system, which in most places is not integrated with other health services.…”
Section: Methodsmentioning
confidence: 99%
“…Relatedly, many studies find high rates of mobility among female sex workers, especially in West and Central Africa, but whether mobility is a risk factor or survival strategy for this vulnerable population is less clear [ 56 , 60 , 61 , 62 , 63 ]. Children and adolescents may move with their caregivers, and they may face additional mobility‐related challenges if attending boarding school [ 64 , 65 ]; this vulnerable population faces many treatment adherence challenges already, which may be compounded by mobility [ 66 , 67 ]. Finally, men who have sex with men (MSM) may experience high rates of mobility and unique challenges for engaging in care, and the few studies available suggest that mobility is associated with worse PrEP and ART outcomes among MSM.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62][63][64] Last, the school environment, especially being in a boarding school has been evaluated in previous studies and shown to negatively influence access to HIV care for children and their treatment outcomes. 65,66 The strength of this study was the utilization of a large data set of program data complemented by survey data from caregivers, which enabled a robust assessment of factors hypothesized to affect viral suppression to undetectable levels. We recognize some limitations in this study, including the reduced generalizability of our findings introduced by only including participants who had more than 1 VL in the study period.…”
Section: Discussionmentioning
confidence: 99%
“…60–64 Last, the school environment, especially being in a boarding school has been evaluated in previous studies and shown to negatively influence access to HIV care for children and their treatment outcomes. 65,66…”
Section: Discussionmentioning
confidence: 99%